Emotions and feelings of (in)justice) in the process of change - Resistance: experiences of informal vendors on the beach, and slum residents in Rio de Janeiro - Reginensi, Caterine (Geografares, 2017)
Based on ethnographic work carried out in three different places of the metropolis of Rio de Janeiro between 2005 and 2010, this paper addresses what is called emotions (fear, anger, shame, hate, love, anger, feelings of (in) justice), which cannot be regarded as simple sensations. The text aims to underline the social character of emotions and observe the ability of various actors to assess conflict situations from the use of emotions. We plan to open a discussion on the role of emotions in the processes change and resistance. Keywords: emotions, change, urban experiences.